Locus of control, optimism, and recollections of depression and self‐reported cognitive functioning following treatment for colorectal cancer. Issue 2 (7th November 2017) - Wilson, Carlene; Giles, Kristy; Nettelbeck, Ted; Hutchinson, Amanda
Abstract: Objective: To investigate the effects of disposition (locus of control, optimism, and depression) on recollections of cognitive functioning following cancer treatment. Methods: Participants were survivors of colorectal cancer (n = 88) and their spouses (n = 40). Survivors retrospectively rated their cognitive functioning and depression, as experienced following treatment and currently rated their dispositions for optimism and locus of control. Survivors' spouses likewise provided their recollections of survivors' cognitive functioning and depression at time following treatment. Results: Correlations between survivors' and spouses' ratings for cognitive functioning were statistically significant but not for depression. Results supported validity of survivors' longer term retrospective reports. Although internal locus of control correlated positively with retrospectively self‐reported cognitive functioning, and negatively with retrospectively self‐reported depression, moderated hierarchical multiple regression found independent contribution of internal locus of control was limited to predicting quality of life; and that, among variables tested, depression correlated strongest with cognitive functioning. Conclusions: Neither internal locus of control nor optimism in colorectal cancer survivors influences correlation between cognition and depression. Health care providers should note individual differences in responses to treatment and be alert to the impact of depression on perceived everyday functioning.